CD34-positive cells and their subpopulations characterized by flow cytometry analyses on the bone marrow of healthy allogenic donors - Carvalho, Jerusa Martins; Souza, Marlon Knabben de; Buccheri, Valéria; Rubens, Cláudia Viviane; Kerbauy, José; Oliveira, José Salvador Rodrigues de (São Paulo Medical Journal, 2009)
CONTEXT AND OBJECTIVE: Counting and separating hematopoietic stem cells from different sources has importance for research and clinical assays. Our aims here were to characterize and quantify hematopoietic cell populations in marrow donors and to evaluate CD34 expression and relate this to engraftment. DESIGN AND SETTING: Cross-sectional study on hematopoietic stem cell assays, using flow cytometry on donor bone marrow samples, for allogenic transplantation patients at two hospitals in São Paulo. METHODS: Immunophenotyping of marrow cells was performed in accordance with positive findings of CD34FITC, CD117PE, CD38PE, CD7FITC, CD33PE, CD10FITC, CD19PE, CD14FITC, CD13PE, CD11cPE, CD15FITIC, CD22PE, CD61FITC and CD56PE monoclonal antibodies in CD45PerCP+ cells, searching for differentiation and maturation regions. CD34+ sorting cells were analyzed for CD38 and CD117. Rh-123 retention was done before and after sorting. Antigen expression and CD34+ cells were correlated with engraftment. RESULTS: In region R1, 0.1% to 2.8% of cells were CD34+/CD45+ and 1.1%, CD34+/CD45-. The main coexpressions of CD45+ cells were CD38, CD22, CD19 and CD56 in R2 and CD33, CD11c, CD14, CD15 and CD61 in R3 and R4. After sorting, 2.2x106 CD34+ cells were equivalent to 4.9% of total cells. Coexpression of CD34+/CD38+ and CD34+/CD117+ occurred in 94.9% and 82% of events, respectively. There was a positive relationship between CD34+ cells and engraftment. More than 80% of marrow cells expressed high Rh-123. CD34+ cell sorting showed that cells in regions of more differentiated lineages retained Rh-123 more intensively than in primitive lineage regions. CONCLUSION: We advocate that true stem cells are CD34+/CD45-/CD38-/low-Rh-123 accumulations.